Museums of world religions: displaying the divine, shaping cultures - Orzech, Charles D. (Bloomsburg Studies in material religion, 2020)
Critically examining the notion of 'world religions', Charles Orzech examines and compares five purpose-built museums of world religions, as well as a number of online sites structured according to the category. These museums are located in Europe (Marburg, Glasgow and St Petersburg), North America (Quebec) and Asia (Taipei) and, inspired by the 19th and 20th-century discipline of comparative religions, museums now seek to promote religious tolerance by representing religious diversity and by arguing for underlying kinship among religions. 0Each museum advances a particular cultural history, and this book shows how the curation of the objects they contain shapes public perceptions of religion, giving material form to the discourses about religion and world religions. Raising important questions about religion and secularity, museum displays and religious piety, World Religions Museums questions the ideology that informs these museums. Building on recent anthropological work on the agency of religious objects, the author both critiques and suggests new approaches to displaying the matter of religion